Analisis Faktor-Faktor Yang Mempengaruhi Turnover Intention Perawat - Ajeng Puspa Indah; Rindu Rindu; Mustopa Mustopa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The emergence of turnover generally begins with turnover intentions (intention to leave) from employees. There are several factors that influence a nurse's intention to leave their job, namely individual characteristics such as age, gender, education level, length of service, marital status, work status, socio-economic conditions, and level of satisfaction. Objective: to determine the factors that influence nurse turnover intention. This type of quantitative research uses a cross sectional design method with a sample size of 105 respondents. The data collection technique uses a questionnaire. Data analysis in this study used the chie square test. Results: The turnover intention rate for nurses at Azra Hospital is quite high, namely 54.3%, the majority of nurses answered that they were dissatisfied with compensation 61%, supervision 50.5%, career development 56.2%, coworkers 50.5%, organizational policies 51.4%. Nurse characteristic variables such as age, marital status, work status, length of service and satisfaction variables regarding compensation, supervision, career development, co-workers and organizational policies have an influence on nurse turnover intention at Azra Hospital. Conclusion: The high level of nurse turnover intention is influenced by nurse characteristic factors, such as young age, marital status, work status as a contract employee, and length of service. The level of dissatisfaction in aspects of job satisfaction, especially those related to compensation, supervision, career development, coworkers, and organizational policies, can trigger nurse turnover intention.